Legal Relationship between TikTok Affiliates and TikTok Sellers after the Enactment of Ministry of Trade Regulation No. 31 of 2023 under Sharia Economic Law - Ryan Ivan Bahtiar; Faizal, Bhismoadi Tri Wahyu; Akhmad Farid Mawardi Sufyan (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
The existence of a legal relationship often underlies collaboration between parties, including between TikTok affiliates and TikTok sellers. The enactment of Ministry of Trade Regulation No. 31 of 2023 has changed the mechanism of TikTok's affiliate system, affecting the legal relationship between these parties. However, previous studies have not adequately explored the legal implications of these changes, particularly from the perspective of Sharia economic law. This study is a normative-empirical legal research employing a qualitative method and a juridical-sociological approach. Data were collected through observation, literature review, and interviews. The study distinguishes itself by combining doctrinal legal analysis with field-based empirical insights and by incorporating Islamic legal principles into digital commercial practices. The findings categorize TikTok affiliate mechanisms into two types. First, commission-based affiliates do not require prior approval from sellers, thus lacking a formal legal relationship. Second, affiliates who enter into cooperation contracts with sellers, which implies a legal relationship, although often weakened by the informal nature of these agreements. From the perspective of Sharia economic law, the first category aligns with a ju’alah contract, while the second involves a valid work-based contract. The study contributes new insights into the classification and legal strength of digital affiliate relationships under both state and Sharia law, especially in light of recent regulatory reforms